Monoclonal antibodies against boar acrosomal antigens labelling undamaged acrosomes of spermatozoa in immunofluorescence test - Peknicová, J; Moos, J (Andrologia, 1990)
Monoclonal antibodies specific for acrosomal proteins were prepared and characterized. Two of these monoclonal antibodies, ACR.3 and ACR.11, reacted with the same molecular specificity of acrosomal antigens (18-20 kDa), antibody ACR.4 reacted with the 25-27 kDa antigens, and antibody ACR.2 reacted with several forms of boar acrosin (55, 53, 45, and 38 kDa). All monoclonal antibodies labelled the acrosomes of undamaged spermatozoa in immunofluorescence test. This test should be convenient as an immunological test of the sperm quality.
Keywords: Animals; Electrophoresis, Polyacrylamide Gel; akrosin; Blotting, Western; Antibodies, Monoclonal; Antigens; antigeny; fluorescenční protilátková technika; Fluorescent Antibody Technique; prasata; Acrosome; Proteins; western blotting; proteiny; Male; Swine; monoklonální protilátky; akrozom; Acrosin; zvířata; mužské pohlaví; elektroforéza v polyakrylamidovém gelu